Shiv-stuti : vavidhya evam parampara - Pandey, Surendra kumar; Author is an IAS (New Delhi D. P. S. Publishing, 2024)
Shiv-Stuti : Vavidhya Evam Parampara
Keywords: Religious Mythology-Hindusim; Religious Mythology-Shivism; Author is an IAS